Answer:
slope= -3
y-intercept= 6
Step-by-step explanation:
1. Approach
To solve this problem, one needs the slope and the y-intercept. First, one will solve for the slope, using the given points, then input it into the equation of a line in slope-intercept form. The one can solve for the y-intercept.
2.Solve for the slope
The formula to find the slope of a line is;
![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
Where (m) is the variable used to represent the slope.
Use the first two given points, and solve;
(1, 3), (2, 0)
Substitute in,
![\frac{(0)-(3)}{(2)-(1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%280%29-%283%29%7D%7B%282%29-%281%29%7D)
Simplify;
![\frac{-3}{1}\\\\=-3](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B1%7D%5C%5C%5C%5C%3D-3)
3. Put equation into slope-intercept form
The equation of a line in slope-intercept form is;
![y = mx + b](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20b)
Where (m) is the slope, and (b) is the y-intercept.
Since one solved for the slope, substitute that in, then substitute in another point, and solve for the parameter (b).
![y=-3x+b](https://tex.z-dn.net/?f=y%3D-3x%2Bb)
Substitute in point (3, -3)
![-3=-3(3)+b\\-3 = -9 + b\\6 = b](https://tex.z-dn.net/?f=-3%3D-3%283%29%2Bb%5C%5C-3%20%3D%20-9%20%2B%20b%5C%5C6%20%3D%20b)